The effectiveness of the tahriri examination as an instrument for measuring students' understanding at Al-Hikmah Tulungagung Islamic Boarding School - Eva Kumalasari; Nayla Wirdatun Ni’ammah; Chusnul Chotimah (Eduvista: Journal of Education and Innovation, 2026)
The effectiveness of the tahriri examination as an assessment instrument in Islamic boarding schools remains debated because empirical evidence linking it to students' level of understanding is still limited. This study aimed to describe students' level of understanding, evaluate the effectiveness of the tahriri examination, and analyze the relationship between the tahriri examination and students' level of understanding at Al-Hikmah Tulungagung Islamic Boarding School for University Students. A quantitative descriptive-correlational design was employed involving 57 santri selected through purposive sampling, with data analyzed using descriptive statistics and Spearman's rank correlation. The findings revealed that the instrument met the validity requirements (9 of 10 items were valid) and demonstrated high reliability (Cronbach's Alpha = 0.866). The effectiveness of the tahriri examination reached 87.6%, students' level of understanding reached 86.9%, and a strong positive and statistically significant relationship was identified between the two variables (r = 0.757, p < 0.001). This study provides empirical evidence supporting the effectiveness of the tahriri examination and proposes a conceptual framework for improving learning assessment in Islamic boarding schools. Abstrak Ketepatan ujian tahriri sebagai instrumen evaluasi pembelajaran di pesantren masih diperdebatkan karena belum banyak penelitian yang membuktikan hubungannya dengan tingkat pemahaman santri secara empiris. Penelitian ini bertujuan mendeskripsikan tingkat pemahaman santri, mengukur efektivitas ujian tahriri, serta menganalisis hubungan antara ujian tahriri dan tingkat pemahaman santri di Pesantren Mahasiswa Al-Hikmah Tulungagung. Penelitian menggunakan pendekatan kuantitatif dengan desain deskriptif-korelasional terhadap 57 santri yang dipilih melalui purposive sampling, kemudian dianalisis menggunakan statistik deskriptif dan korelasi Spearman Rank. Hasil penelitian menunjukkan bahwa instrumen memenuhi kriteria validitas (9 dari 10 butir valid) dan reliabilitas tinggi (Cronbach's Alpha = 0,866), tingkat efektivitas ujian tahriri mencapai 87,6%, tingkat pemahaman santri sebesar 86,9%, serta terdapat hubungan positif yang kuat dan signifikan antara kedua variabel (r = 0,757; p < 0,001). Penelitian ini memberikan bukti empiris bahwa ujian tahriri merupakan instrumen evaluasi yang efektif serta menawarkan kerangka konseptual sebagai acuan pengembangan evaluasi pembelajaran di pesantren.